Cross-Border M&A and Innovative Activity: Firm-Level Evidence - Joel Stiebale (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper provides empirical evidence on the relationship between cross-border mergers and acquisitions (M&A) and innovation. For the empirical analysis a unique firm-level data set is constructed that combines balance sheet data and an M&A database with information on patent applications. Within three years after a cross-border M&A, patent applications filed by the merged entity increase by more than 30%. Splitting patent applications by the inventors country it is found that the positive association with post-merger patenting is mainly driven by patents invented in the countries of the acquirers headquarter and its previous subsidiaries. In contrast, there is on average a decrease in patent applications invented in the targets country of more than 60%. Accounting for endogeneity of international acquisitions by estimating dynamic count data models and applying instrumental variable techniques, the results indicate that part of this correlation stems from a causal effect.
Keywords: D22; F23; G34; 330